Strategi Kemenangan Anggota Legislatif terpilih di Dapil 1 Kabupaten Musi Banyuasin Tahun 2024 - Aldi, Muhammad; Febriyanti , Doris; Amaliatulwalidain , Amaliatulwalidain (Jurnal Studi Ilmu Sosial dan Politik, 2023)
Purpose: This research aims to identify and analyze Mr Tapriansyah's offensive strategy in the 2024 legislative elections in Musi Banyuasin Regency. Offensive strategy is divided into two methods. First, expanding the market through the Social Assistance Program, Yasin Recitation Routine Program, Maternal and Child Health Education Campaign, Offer of Free Education Policy and Infrastructure Development, and Involving Local Religious Figures in tadarus activities. Research methodology: This research uses qualitative methods with data collection techniques through observation, interviews, questionnaires and documentation. Researchers visit the research object directly to observe the focus elements. In-depth interviews were conducted with candidates and parties involved in campaigns and elections. Data is documented to support research results. The digital questionnaire was distributed via Google Form to 100 residents of Musi Banyuasin Regency. Results: Research shows that Mr. Tapriansyah has succeeded in implementing the strategy of expanding market expansion well. The campaign program which includes social assistance and regular Yasin recitations has been successfully implemented, involving local religious leaders. Limitations: Researchers and resource persons in this study are in different locations. The researcher is domiciled in Palembang City, while the resource person is in Musi Banyuasin Regency. Researchers continue to conduct direct interviews with research sources. However, to overcome distance constraints, the researcher conducted an interview with one of the sources via the WhatsApp application. Contribution: This research contributes to the political campaign strategy literature by demonstrating successful strategy implementation.